An investigation of the visual and systemic symptoms among computer users at the National Home Builders' Registration Council and British Petroleum in Johannesburg, Gauteng Province, South Africa - Mogane, Joyce Pheladi (University of Limpopo (Turfloop Campus), 2014)
Topic An investigation of the visual and systemic symptoms experienced by computer users at the National Home Builders’ Registration Council (NHBRC) and British Petroleum (BP) in Johannesburg, Gauteng Province, South Africa. Background The repetitive use of computers in the working places results in the visual and ergonomic disorders that affect the computer users adversely. The computer users experience fatigue which causes visual symptoms such as eyestrain, blurred vision, heaviness of the eyelids or forehead, dry eyes, sensitivity to light and irritatedeyes. The ergonomic disorders like neck pain, backache and wrist pain are also experienced by computer users. These conditions are collectively called Computer Vision Syndrome which is considered as an occupational hazard. Uncorrected refractive errors and binocular anomalies can contribute to these symptoms. The visual and systemic symptoms that affect the computer users in the workplace need to be investigated. Purpose The purpose of the study was to subjectively investigate the visual and systemic symptoms experienced by computer users in the two selected companies in Gauteng Province South Africa. Methodology Structured questions, (open and close ended) were used to obtain information needed for this study. The questions covered demographic as well as information relating to the use of the computer such as the duration of working on computer, the offices/working environment, the appearance and the distance of the screen to the eyes, the working station and visual devices et cetera. Results Participants included 47 (72.3%) females and 17 (26.2%) males and their ages ranged from 20 to 59 years with the mean of 39.5 and the standard deviation of ± 13.1years. Many (80%) of the participants between the ages of 20 to 29 years reported experiencing eye strain. The highest (75%) percentage of slow refocus was reported by the participants that were between the ages of 30 to 39 years. Most males (58.8%) reported experiencing eye strain, slow refocus and headaches associated with computer use. The majority of the females (63.8%) reported experiencing eye strain, while (59.6%) experienced slow refocus and (51.1%) suffered from headaches. A higher percentage of males (23.5%) experienced wrist pain while lower (14.9%) of females experienced wrist pain. No males (0.0%) reported back pain and only a small (8.5%) of females reported back pain. Conclusion Based on the above findings, it is concluded that visual and the systemic symptoms associated with the use of the computer affected most of the workers from the two companies. The factors that may lead to the various symptoms experienced may be ergonomic (environmental) or visual or a combination of these. The environmental factors can be the angle of gaze to the computer screen or the illumination of the working area, while visual factors could be uncorrected refractive error or binocular anomaly. Other factors may include age and working for prolonged time looking at the computer monitor. These factors may then leads to symptoms like eye strain, slow refocus, blurred vision, headaches, dry eyes and systemic symptoms such as neck pain.
Thesis (MPH) --University of Limpopo, 2014
Keywords: Visual and Systemic Symptoms; Computer Users; British Petroleum; National Home Builders' Registration Council - Johannesburg - Gauteng; Computer vision syndrome; Computer users